Hypothesis to Explain the Occurrence of Multiple Peaks of DFL in Nerve Conduction Measurement (Bangladesh Journal of Medical Physics, 2013)
Distribution of F-Latency (DFL) is a new nerve conduction parameter obtained using evoked EMG responses, and was introduced by us earlier. We had established that DFL is simply related to the distribution of conduction velocity (DCV) of motor fibres in a peripheral nerve, as an approximate mirror image. Normally DFL has a single peak for healthy nerves, but double, or sometimes, triple peaks of DFL were observed in the median nerve, recording the evoked EMG responses from the Thenar muscle in the palm of the hand. From observation, we also established that such multiple peaks of DFL are associated with Cervical Spondylosis (CS). Double peaks were also observed on the nerves of legs suggesting association with Lumbo-sacral spondylotic neuropathy. The present work puts forward hypotheses to explain the occurrence of double or triple peaks of DFL from median nerve in CS, based on principles of physics, physiology and mathematics, and relate these to observations. This includes observations reported in our earlier work, and also obtained from hundreds of patients tested at a clinic managed by the author. The hypothesis assumes similar DCV with single peaks for all the nerve branches that combine to form the median nerve. Compression or degeneation of one or two of the above nerve branches will result in differential shifts of DFLs, and therefore a combination in the median nerve will give rise to double or triple peaks. Initially the explanation was based on radiculopathy, but the hypotheses evolved when newer neuropathological conditions like myelopathy, and external nerve injury were observed. Finally a generalized hypothesis has been put forward that would cover all these abnormal conditions that affect a peripheral nerve of a limb, both in the hands and the legs. Experiments have been suggested that may test these hypotheses, which, if successful, will lead to a greater understanding of neurophysiology and provide a simple and sensitive diagnostic test through the use of DFL. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14675 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 27-36